Pengaruh Kecukupan Modal dan BOPO terhadap Laba Operasi pada BUMDes di Kecamatan Banjar - Kadek Yuyun Tamara Dewi; Gede Putu Agus Jana Susila (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study aims to examine the effect of capital adequacy ratio and operational cost with operational income on operating income simultaneously or partially. This research design used causal quantitative. The subject of this research is Village Owned Enterprises in Banjar District and the object of research is capital adequacy ratio, operational cost with operational income and operating income. The sampling technique used was purposive sampling with a sample size of six Village Owned Enterprises. Data were collected by recording documents, then analyzed by multiple linear regression analysis. The results showed that (1) capital adequacy ratio and operational cost with operational income had a significant effect on operating income with an influence contribution of  46.2% (2) capital adequacy ratio had a negative and not significant effect on operating income with an influence contribution of 0.3% (3) operating cost with operational income had a negative and significant effect on operating income with an influence contribution of 46.1%.